2020
DOI: 10.1101/2020.02.03.931634
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Zebrafish Kit ligands cooperate with erythropoietin to promote erythroid cell expansion

Abstract: Key points:• Kit signaling contributes to erythroid cell development and is conserved from fish to man • Ex vivo expansion and self-renewal of zebrafish erythroid progenitors requires addition of recombinant Kitlga AbstractKit ligand (Kitlg) is pleiotropic cytokine with a prominent role in vertebrate erythropoiesis. Although the role of Kitlg in this process has not yet been reported in Danio rerio (zebrafish), in the present study, we show that its function is evolutionary conserved. Zebrafish possess two cop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…EPO can promote the proliferation of erythrocytes, induce differentiation, maintain normal osmotic pressure inside and outside the membrane, and stimulate multidirectional progenitor cells, megakaryocyte progenitor cells and granuloprogenitor cells to some extent. 142,143 Lymphocytes are the basis of animal immunity. The structure of lymphocytes has not changed much during species evolution.…”
Section: Blood Cell Morphology and Physiology In Fishmentioning
confidence: 99%
See 1 more Smart Citation
“…EPO can promote the proliferation of erythrocytes, induce differentiation, maintain normal osmotic pressure inside and outside the membrane, and stimulate multidirectional progenitor cells, megakaryocyte progenitor cells and granuloprogenitor cells to some extent. 142,143 Lymphocytes are the basis of animal immunity. The structure of lymphocytes has not changed much during species evolution.…”
Section: Blood Cell Morphology and Physiology In Fishmentioning
confidence: 99%
“…Studies have shown that EPO mainly acts on erythroid progenitor cells, presumably through the action of genetic deblocking factors that determine haemoglobin synthesis. EPO can promote the proliferation of erythrocytes, induce differentiation, maintain normal osmotic pressure inside and outside the membrane, and stimulate multidirectional progenitor cells, megakaryocyte progenitor cells and granuloprogenitor cells to some extent 142,143 …”
Section: Blood Physiological Indexmentioning
confidence: 99%